Relation between the TIMI frame count and the degree of microvascular injury after primary coronary angioplasty in patients with acute anterior myocardial infarction. Issue 1 (16th December 2004) - Ohara, Y; Hiasa, Y; Takahashi, T; Yamaguchi, K; Ogura, R; Ogata, T; Yuba, K; Kusunoki, K; Hosokawa, S; Kishi, K; Ohtani, R
Abstract : Objective: To investigate the relation between thrombolysis in myocardial infarction (TIMI) frame count (TFC) and coronary blood flow velocity (CBFV) parameters reflecting the degree of microvascular injury in patients with acute myocardial infarction. Results: TFC and CBFV were measured after primary coronary angioplasty in 103 consecutive patients with their first anterior wall acute myocardial infarction. TFC correlated inversely with the averaged peak velocity ( r = −0.43, p < 0.0001). However, TFC did not correlate significantly with diastolic deceleration time and with the averaged systolic peak velocity ( r = −0.16, p = 0.22, and r = −0.23, p = 0.16, respectively). The patients were divided into two groups according to presence (35 patients) or absence (68 patients) of systolic flow reversal. There was no significant difference in TFC between the two groups (29 (16) v 25 (13), p = 0.20). Conclusions: These findings suggest that the TFC reflects epicardial CBFV. However, it is not accurate enough to assess the degree of microvascular injury after primary coronary angioplasty.